Faculty Recruitment Practices and SDG4: Challenges and Recommendations - AlRasbi Nassr; Yeravdekar Vidya; Neelam Netra (Australasian Accounting, Business and Finance Journal, 2023)
This article aims to critically study the literature on the challenges H.E.I.s (Higher Education Institutions) encounter while recruiting faculties and provide opportunities for other researchers to use it as a foundation for future research. The reviewed literature begins broadly with recruitment to gain a comprehensive knowledge of the concept, its origin, differential usage through several decades, and various factors that influenced its effectiveness. Accordingly, the authors did an extensive study considering the breadth and depth of the core problem of the study. The study of the challenges of faculty recruitment has been undertaken in three phases spanning 60 years, and the authors reviewed the literature critically in each category. The authors also cited relevant, valuable documents in this work from 80 countries -represented individually or collectively- on various factors affecting the recruiting process. They are taking into consideration the importance of SDG4 and relating it to the Oman 2040 Vision, which also includes 12 priority areas. These factors constitute challenges to the entire recruitment process considering three perspectives from the H.E.I., the Recruiter, and the perspective of Faculty. Finally, the summary and conclusion of the article give further directions for other researchers in this domain to use the existing contents with excellent references as guidance in their investigations.
Keywords: Faculty Members; Recruitment; Challenges; HEIs